Analysis of Water Quality and River Waters Microbology for Manifestation of Food Safety - Ujianti, Rizky Muliani Dwi; Androva, Althesa (Advance Sustainable Science, Engineering and Technology, 2019)
Â Abstract. Banjir Kanal Barat is a river in the Garang watershed, Semarang City, Central Java, Indonesia. Its function is as a source of water for the community. The level of pollution in this river is already high. The purpose of this study is to provide advice to governments, communities and related stakeholders to realize integrated river management, and fisheries-based food security is achieved. This research method is: analyzing the water quality of the Banjir Kanal Barat river, and analyzing the amount of faecal and total coliform bacteria content in the Banjir Kanal Barat river, and analyzing how to overcome the decline in the quality of waters of the Banjir Kanal Barat river due to faecal and total coliform bacteria pollution. The results showed that the water quality at the research location was still in the quality standard. The content of coliform dan faecal bacteria at the study site exceeds the quality standard, this is due to the influence of domestic waste from households. The thing that needs to be done is counseling the existence of a clean and healthy life, especially for people who are still throwing domestic waste into the river. The existence of water purification equipment is also very necessary to overcome this problem. Water quality management can be done with policy analysis. Regulations related to water quality management can be analyzed and then given solutions and recommendations related to these rules so that policies can be taken that are sustainable, integrated, and coordinated between various parties in managing river water quality and food security.Â Keywords: food security, water quality, river, faecal coliform, total coliform